Biochemical and Pathological Evaluation of Antibiotic Resistance Patterns and Histopathological Changes in Patients with Chronic Pharyngitis - Aneeka Sarwar, Irshad Ali, Shandana Altaf, Muhammad Bilal, Shameem Bhatti, Amna Akram, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The persistence of the inflammation of the pharyngeal tissues is called chronic pharyngitis and is often complicated by developing antibiotic resistance. Systemic inflammation and adverse tissue remodeling are in part due to the development of resistant bacterial strains that have resulted from the misuse of antibiotics. Optimization of therapeutic strategies in chronic pharyngitis requires an understanding of the biochemical and pathological implications of antibiotic resistance. Methods: In a prospective one-year study, n=70 patients with clinically diagnosed chronic pharyngitis were enrolled and divided into two groups antibiotic sensitive (n = 32) and antibiotic resistant (n = 38). Detailed clinical evaluation was performed on all patients, blood samples were collected for assessing inflammatory markers (CRP, ESR), cytokines (IL6, TNfα), and oxidative stress parameters (MDA, SOD). Microbial identification and antibiotic susceptibility testing were performed on pharyngeal swabs cultured. Furthermore, a subset of patients are permitted to conduct pharyngeal tissue biopsies for histopathological examination. Univariate and multivariate regression models were used to analyze data in SPSS version 26 for determining predictors of elevated inflammatory markers. Results: Compared to the sensitive group (p < 0.005), CRP, ESR, IL6, and TNFα levels were significantly higher in patients with antibiotic-resistant isolates. MDA levels and SOD activity levels were higher in the resistant group (p < 0.01) compared to that of the susceptible group. Results of regression analysis showed that antibiotic resistance was an independent predictor of increased CRP (β = 0.38, p = 0.001) and IL-6 (β = 0.35, p = 0.003). There were more pronounced epithelial hyperplasia, inflammatory infiltrates, and submucosal fibrosis in resistant cases (p = 0.002). Conclusion: Increased inflammation, oxidative stress, and severe tissue alterations are correlated with antibiotic resistance in chronic pharyngitis. These results underscore the necessity of targeted treatments and good antibiotic stewardship. Keywords: Chronic Pharyngitis, Antibiotic Resistance, Inflammation, Oxidative Stress, Histopathology